Nonpolar residues in the presumptive pore‐lining helix of mechanosensitive channel MSL10 influence channel behavior and establish a nonconducting function. (5th June 2018) - Maksaev, Grigory; Shoots, Jennette M.; Ohri, Simran; Haswell, Elizabeth S.
Abstract: Mechanosensitive (MS) ion channels provide a universal mechanism for sensing and responding to increased membrane tension. MscS‐like (MSL) 10 is a relatively well‐studied MS ion channel from Arabidopsis thaliana that is implicated in cell death signaling. The relationship between the amino acid sequence of MSL10 and its conductance, gating tension, and opening and closing kinetics remains unstudied. Here, we identify several nonpolar residues in the presumptive pore‐lining transmembrane helix of MSL10 (TM6) that contribute to these basic channel properties. F553 and I554 are essential for wild type channel conductance and the stability of the open state. G556, a glycine residue located at a predicted kink in TM6, is essential for channel conductance. The increased tension sensitivity of MSL10 compared to close homolog MSL8 may be attributed to F563, but other channel characteristics appear to be dictated by more global differences in structure. Finally, MSL10 F553V and MSL10 G556V provided the necessary tools to establish that MSL10's ability to trigger cell death is independent of its ion channel function.